Aversive effects of volatiles from intact plants help to fine tune host-searching behavior of the parasitoid wasp, Cotesia kariyai - Ross, Socheat; Matsuyama, Shigeru; Furukawa, Seiichi; Kuramitsu, Kazumu; Kainoh, Yooichi (Frontiers in Ecology and Evolution, 2023)
Herbivore-induced plant volatiles (HIPVs) from infested plants are exploited by parasitoid wasps as cues to search for host habitat. However, uninfested (intact) and infested plants are often intermingled in nature, and how volatiles released by intact plants affect host-searching behavior in natural habitats remains unknown. In a previous study, using a wind tunnel, we found that intact maize plants negatively influenced host-searching behavior of a parasitoid wasp, Cotesia kariyai (Hymenoptera: Braconidae), when they were placed downwind of infested plants. To determine whether intact plant volatiles affect host searching by C. kariyai, we collected volatiles from intact plants using a headspace volatile collection technique. In a wind tunnel, wasps landed less frequently on a green paper model treated with intact plant volatiles placed in front of an infested plant, than on a green paper model treated with the solvent, hexane. In a 4-arm olfactometer, wasps spent significantly less time in an arena containing mixed volatiles from intact and infested plants, compared to the same arena treated only with volatiles from infested plants. Both results indicate that intact plant volatiles re-direct host-searching behavior in C. kariyai females. Chemical analyses suggested differences in volatiles between intact and infested plants. In terms of parasitoid adaptations for effective searching for hosts in complex environments, aversive effects of intact plant volatiles may help C. kariyai to locate patches of infested plants.